154 Impact of Post-Breeding Feeding Level on the Reproductive Performance of Sows. (12th April 2022) - Anderson, Brooke; Paz, Ximena; Porta, Alina; Rosero, David
Abstract: The objective of this study was to determine the impact of feeding sows different feed levels during the first 7 d of gestation on the reproductive performance of sows. A total of 483 sows (Camborough, PIC) were used, equally balanced by parity (3-10) and body condition score (BCS) and placed on 1 of 2 treatments after breeding. Treatments consisted of: 1) feed a common level of 1.81 kg/d regardless of BCS from breeding to d 7, then feed levels were adjusted according to BCS thereafter; and 2) adjustment of feed level at breeding according to BCS. Sows were fed either 3.63, 2.72, 2.04, or 1.59 kg/d according to their BCS (1-5), respectively. Body condition, measured by the sow caliper, was reassessed, and feed levels were adjusted as needed on d 45 and 90 of gestation. Diets consisted of a standard milo and wheat midds based gestation diet which met or exceeded NRC (2012) recommendations for nutrient levels. Feeding thin (BCS 1, 2) pregnant sows elevated feed levels from breeding to d 7 of gestation tended to reduce the return rate (% sows that returned to estrus: bred) ( P = 0.098; 8.85 vs. 3.68%, respectively); but not the farrow rate (% sows that farrowed: bred; P = 0.265, 87.61 vs. 91.91%, respectively). There was no difference in litter size at farrowing ( P > 0.10). In conclusion, feeding weaned sows according to body condition compared with feeding 1.81 kg/d during the first 7 d of gestation decreased the number of thin sows returning to estrus.